Management of polluting waste from sugarcane industries in the state of Alagoas, Brazil - Novais, Roney Calheiros de; Magalhães, Ivomberg Dourado; Gonzaga, Giordano Bruno Medeiros; Silva, Jailson Valério da; Melo, Augusto César Cardoso de; Medeiros, Aldair de Souza (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
Despite the environmental impacts generated by polluting waste from the sugar-energy industry, studies evaluating this issue in the Northeast region of Brazil are still incipient. Therefore, the aim of this study was to evaluate the environmental impacts of polluting waste produced by sugarcane industries in the state of Alagoas. A survey was carried out, applying a questionnaire in three mill and an autonomous distillery, located in the state of Alagoas. The mills are identified in this study as mills A, B, C and D. The four mills carried out the fermentation in fed batches (batch fed process) and have a lung chamber. Two have open vats and two closed fermentors, for recovering the ethanol dragged by the gases given off during the ethanol fermentation. The questionnaire was filled out by those responsible with operational data from each mill. Sugarcane crushing, sugar production, hydrous ethanol production, anhydrous ethanol production, kg of sugar per ton of cane and liters of ethanol per ton of cane, consumption of sulfuric acid and cyclohexane were evaluated; water used to wash the sugarcane and wash the gases released during fermentation. The sugarcane mills in the state of Alagoas evaluated in this study, which produce sugar and ethanol, in addition to other marketable by-products, use production methods and processes with a high potential for environmental impact.